E-TRUST AND E-SERVICES FOR THE HALAL PRODUCT IN JAPAN - ELSANDRA, YESI; AZMAN, HERU AULIA; YULIANTO, ARDHIAN AGUNG (Universitas Islam Negeri Imam Bonjol Padang, 2022)
The aim of the research is to describe the halal product among Muslim communities in Japan. Japan provides many facilities to serve halal food in Japan to show enthusiasm become a world role model of halal products. The Muslim community in Japan practices online transactions between them and they bought halal products in e-commerce by word of mouth. Most of the halal products in Japan are imported from Muslim countries. For the Indonesian Muslim community in Japan, e- trust becomes an important instrument for deciding to buy online halal products. Descriptive qualitative research is conducted to describe the fact, conditions, and phenomena regarding the halal industry in Japan. The result shows that the Muslim community in Japan needs the availability of halal products and services. E-trust and e-services to a halal online store became an important role to influence the Muslim community in Japan in making transactions.